Carbon allocation of Chinese pine seedlings along a nitrogen addition gradient - Wang, Guoliang; liu, Fang (Forest ecology and management, 2014)
•We grew pine seedlings across an N gradient and traced the short-term C allocation.•Seedling physiological performance exhibited a modal response.•Response of biomass ratio to N addition supports functional equilibrium hypothesis.•Allocation of C to fine roots supports a “shared control” concept.•Increasing soil N supply affects pine seedling physiology and root carbon supply. The response of carbon (C) allocation in pine seedlings to a gradient of nitrogen (N) addition was evaluated to examine the effects of increasing N deposition on forest trees. Seedlings of Pinus tabulaeformis were subject to N addition treatments (0–22.4gNm−2yr−1) for 3years and the short-term allocation of a 13C photosynthetic pulse into leaves, stems, different order roots and soil was traced. Photosynthetic rate, roots respiration, biomass and N concentration of foliage and roots with root branching orders were also measured. It was found that the physiological performance of seedlings exhibited a modal response, peaking at 11.2gNm−2yr−1. The highest N treatment (22.4gNm−2yr−1) had detrimental effects on seedling physiological function (photosynthesis, root respiration) and was strongly decoupled from N concentrations in plant tissues. In agreement with the functional equilibrium hypothesis, root:leaf biomass ratio declined with N addition up to 11.2gNm−2yr−1. The hypothesis states that a stable ratio of resource acquisition by shoots and roots is maintained in the face of constraints, so that one organ does not greatly outgrow the other and overall plant performance is optimized. This response was most pronounced when expressed on the basis of the lowest order roots. Allocation of C to fine roots compared to coarse roots increased with N availability up to the highest N treatment. Soil C flux declined significantly with excess N supply. The results support a “shared control” concept of root C allocation, in which the allocation of C to roots depends on both supply from the shoot and demand from the roots. This provides new insights into the effects of increasing soil N supply on pine seedling physiology and root carbon supply.